FACTORS AFFECTING THE IMPLEMENTATION OF PRIMARY HEALTH SERVICES AT COMMUNITY HEALTH CENTERS: HEALTHCARE WORKERS’ PERSPECTIVE - Permana, Adrian; Fitria, Ida Jalilah (PT. Altin Riset Publishing, 2025)
This study aims to identify the factors influencing the implementation of prime service at Melong Asih Community Health Center from the perspective of health workers. Employing a qualitative approach, this research involved in-depth interviews with health workers and direct observation. The findings revealed that responsiveness, accessibility, communication, politeness, and the availability of medicines are key factors affecting the quality of service. Although Melong Asih Community Health Center has shown a strong commitment to providing quality services, there are still several aspects that need to be improved, such as consistency in providing friendly and empathetic services, improving administrative systems, and enhancing the competence of health workers. This research provides important implications for efforts to improve the quality of services at Melong Asih Community Health Center, namely by enhancing the competence of health workers, improving administrative systems, and ensuring the availability of adequate resources.